A Comparative Study on Students’ Grammar Achievement Taught by Lecture and Inquiry Methods - Sri Haryanti; Kustinah Kustinah; Sukasih Ratna Widayanti (International Journal of Active Learning, 2023)
Mastery of grammar/structure is central to mastery of language skills. Without mastering structure, students will have difficulty expressing their thoughts both orally and in written. Based on several years of teaching experience, researchers know that most students have succeeded in mastering lecture material through the lecture method. The researchers formulated two problems: 1) Is there a significant difference in structure learning achievement between students taught through lecture and inquiry methods?, 2) Which method results better structure learning achievement?.The population of this study are the third semester students of the English Education Study Program, Widya Dharma University of Klaten for the 2022/2023 Academic Year with a total of 20 students. The sampling technique used was purposive sampling. The independent variables in this study were students who were taught by lecture and inquiry methods. While the dependent variable was structure learning achievement. Researchers used the test method to collect data. The content validity of the test used was tested by comparing the content of the test with the content of the material taught in semester III. The data analysis method used was a statistical method of t-test. The mean of students taught by the lecture method is 76.6, and by the inquiry method is 73.91. The t-test calculation result ofÂ 0.181 does not fulfill any of the t-table lists, so there is no significant difference in structure learning achievement between students taught through lecture and inquiry methods; and lecture method is better at producing structure learning achievement.Â